2013
DOI: 10.1093/humrep/det271
|View full text |Cite
|
Sign up to set email alerts
|

Single-nucleotide polymorphism microarray-based preimplantation genetic diagnosis is likely to improve the clinical outcome for translocation carriers

Abstract: The adoption of SNP-PGD combined with TE biopsy and FET may significantly improve the clinical pregnancy rate, and decrease the miscarriage rate after PGD for translocation carriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(68 citation statements)
references
References 27 publications
4
64
0
Order By: Relevance
“…The percentage of normal chromosomes determined in this study is consistent with that of normal chromosomes in fresh biopsy cycles (42.3%) reported in our previous study (19). Therefore, it can be said that the test-failure blastocysts still have a high percentage of normal chromosomes.…”
Section: Discussionsupporting
confidence: 91%
“…The percentage of normal chromosomes determined in this study is consistent with that of normal chromosomes in fresh biopsy cycles (42.3%) reported in our previous study (19). Therefore, it can be said that the test-failure blastocysts still have a high percentage of normal chromosomes.…”
Section: Discussionsupporting
confidence: 91%
“…Preimplantation genetic diagnosis (PGD) based on fluorescence in situ hybridization (FISH) (Conn et al 1998, Van Assche et al 1999, Coonen et al 2000, Alves et al 2002, Otani et al 2006, Bernicot et al 2010, Bernicot et al 2012, Ko et al 2013 and microarray-based profiling , Fiorentino et al 2011, Treff et al 2011, van Uum et al 2012, Huang et al 2013, Tan et al 2013 are widely used to select normal/balanced embryos for CR carriers to transfer.…”
Section: Introductionmentioning
confidence: 99%
“…FISH is also used to determine translocations. However, this field of study has now been successfully replaced by methods that are more reliable and precise, such as SNP [16] and NGS [17].…”
Section: Fluorescent In Situ Hybridization (Fish)mentioning
confidence: 99%
“…As a result of the combined activities of a research team, a high implantation rate and low miscarriage rate was observed in infertile couples [30]. Studies with SNP platforms were also conducted on diagnosis of balanced, unbalanced and Robertsonian translocations, and good outcomes were observed [16].…”
Section: Single Nucleotide Polymorphism (Snp) Analysismentioning
confidence: 99%